2018
DOI: 10.1103/physreve.98.022501
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the variance in the translocation times by prestretching the polymer

Abstract: Langevin dynamics simulations of polymer translocation are performed where the polymer is stretched via two opposing forces applied on the first and last monomer before and during translocation. In this setup, polymer translocation is achieved by imposing a bias between the two pulling forces such that there is net displacement towards the trans side. Under the influence of stretching forces, the elongated polymer ensemble contains less variations in conformations compared to an unstretched ensemble. Simulatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Similar to other coarse‐grained translocation simulations, we used LD to integrate a generic bead spring polymer model of N=100 beads with excluded volume interactions . The Weeks–Chandler–Andersen (WCA) potential is used to model excluded volume interactions .…”
Section: Methodsmentioning
confidence: 99%
“…Similar to other coarse‐grained translocation simulations, we used LD to integrate a generic bead spring polymer model of N=100 beads with excluded volume interactions . The Weeks–Chandler–Andersen (WCA) potential is used to model excluded volume interactions .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that polymers stretched prior to translocation display reduced conformational entropy (and σ/τ values) due to their more elongated conformations [67,72,73].…”
Section: Modulation Of Translocation Time Statisticsmentioning
confidence: 99%
“…Previous studies have shown that polymers stretched prior to translocation display reduced conformational entropy (and σ/τ values) due to their more elongated conformations. 57,63,64 Interpreting σ/τ values as being inversely correlated with the average conformation elongation, Figure 5c should therefore show a non-monotonic relationship between elongation and salt concentration ratio Ctrans/Ccis: For a fixed Ccis and varying Ctrans, capture-opposing ASC conditions (Ctrans/Ccis < 1) result in less elongated polymer conformations than SSC conditions (Ctrans/Ccis = 1), which in turn result in more elongated conformations than capture-promoting ASC conditions (Ctrans/Ccis > 1), with the maximal elongation occurring near Ctrans/Ccis = 1 (see Figure 5d). To further validate the increase of σ/τ in capture-promoting ASC conditions and support the proposed elongation interpretation, the dependence of σ and σ/τ on polymer length is shown in Figure S9.…”
Section: Modulation Of Translocation Time Statisticsmentioning
confidence: 99%